Les écoles et la Constitution - Magnet, Joseph (Les Cahiers de droit, 1983)
The question of education is probably one of the thorniest political problems in Canadian history. English andfrench speaking Canadians have long stood divided on the matter. In the first part of his article, the author describes the effect of two specific clauses of article 93 of the BNA Act on the nation's schools. Much of the hostility felt by Canada's major linguistic groups can, from his point of view, be linked to these two provisions. In the second part, he discusses the recent constitutional reforms and expresses the hope that the new agreement, if correctly implemented, will bring about the long-awaited reconciliation between Canada's linguistic communities.